1992
DOI: 10.1099/0022-1317-73-2-375
|View full text |Cite
|
Sign up to set email alerts
|

Protection of mice from lethal influenza by defective interfering virus: T cell responses

Abstract: The immune-mediated lethal influenza in C3H/He-mg (H-2 k) mice infected with A/WSN influenza virus (H1N1) was investigated. A primary class I major histocompatibility complex-restricted, CD8 ÷ cytotoxic T lymphocyte (CTL) response was found in the lungs with a peak activity at 5 days post-infection. Monoclonal antibody depletion in vivo showed that a lethal CD8 + cell response as well as a lethal CD4 ÷ response was generated during infection. Mice survived infection only if both CD8 ÷ and CD4 ÷ cells were depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Earlier, the importance of T lymphocytes in host-dependent pathology was already reported in the context of influenza virus infection in mice (29), where depletion of CD4 ϩ and CD8 ϩ T cells before influenza inoculation prevented morbidity, in agreement with our findings. However, the interplay of these populations is still unclear; depletion of CD4 ϩ cells might result in lack of help to pathological CD8 ϩ cells.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier, the importance of T lymphocytes in host-dependent pathology was already reported in the context of influenza virus infection in mice (29), where depletion of CD4 ϩ and CD8 ϩ T cells before influenza inoculation prevented morbidity, in agreement with our findings. However, the interplay of these populations is still unclear; depletion of CD4 ϩ cells might result in lack of help to pathological CD8 ϩ cells.…”
Section: Discussionsupporting
confidence: 93%
“…Analysis of the specificity of T cell responses using vaccinia viruses expressing individual influenza A virus proteins showed that, unusually for influenza A virus infections, the response in A/WSN-infected, DI virus-treated mice was largely strain specific. Depletion of both CD8 + and CD4 + cells with specific antibody was needed to abolish lung consolidation and for mice infected with A/WSN or A/WSN + inactivated DI virus to survive [19], but like the SCID mice reported here, infectious virus in the lung was not cleared. In contrast, when mice depleted of CD8 + and CD4 + cells were inoculated with A/WSN + DI virus, lung infectivity was cleared, presumably with the assistance of local, T cell-independent, virus-specific antibody.…”
Section: Discussionmentioning
confidence: 77%
“…These mice all died. CTL responses were diminished in mice inoculated with A/WSN + DI virus and these all survived [19]. Analysis of the specificity of T cell responses using vaccinia viruses expressing individual influenza A virus proteins showed that, unusually for influenza A virus infections, the response in A/WSN-infected, DI virus-treated mice was largely strain specific.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this is in line with the almost universal reassortment of full-length RNAs which takes place between influenza A strains, for which a requirement for mutual replication and encapsidation is mandatory. Nonetheless, this interaction is not universal as DI WSN did not protect mice against PR8 (McLain et al, 1992;unpublished data).…”
Section: Discussionmentioning
confidence: 98%